(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
The study was carried out to evaluate the clinical efficacy of Mineral trioxide aggregate (MTA) in arresting dental resorption and as a regenerative material especially for growth of bone and periodontal ligament. Tooth no 25 having Aggressive Dental Resorption (simultaneous presentation of apical and lateral perforating resorption) with discharging sinus and co-existing oral communication through periodontal pocket was treated with MTA. After thorough debridement and disinfection of the root canal, complete obturation of the root canal system was done with MTA and evaluated thereafter. Follow up examinations up to a period of 1 year could not reveal resolution of any of the preoperative signs and symptoms i.e. discharging sinus, periodontal pocket healing and mobility; also did not show radiographic evidence of arrest of resorption and bone or periodontal tissue formation. Clinical efficacy of MTA in arresting dental resorption with subsequent repair found questionable. However, Shorter period of disinfection, co-existence of oral communication with the resorptive defects through periodontium and non surgical treatment approach all or any one of these may be the concern for the failure. Keywords: Resorption, Perforation, MTA. DOI: 10.3329/bsmmuj.v2i1.3711 BSMMU J 2009; 2(1): 42-46